1993
DOI: 10.1177/41.11.8409368
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural immunogold localization of tumor necrosis factor-alpha to the matrix compartment of eosinophil secondary granules in patients with idiopathic hypereosinophilic syndrome.

Abstract: Peripheral blood eosinophils from two normal donors and two patients with the hypereosinophilic syndrome (HES) were analyzed with a post-embedding immunogold method to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 4 publications
0
41
0
Order By: Relevance
“…The first cytokine found within lipid bodies was tumor necrosis factor-alpha (TNF-α). TNF-α was detected within cytoplasmic lipid bodies of several cell types present on colonic Crohn's disease biopsies, including infiltrating eosinophils (Beil et al 1993). Recently, TNF-α was also found within lipid bodies of circulating neutrophils of septic patients and murine infiltrating neutrophils of experimentally induced sepsis (Pacheco et al 2002).…”
Section: Are Pre-formed Cytokines Stored Within Other Eosinophil Intrmentioning
confidence: 99%
See 2 more Smart Citations
“…The first cytokine found within lipid bodies was tumor necrosis factor-alpha (TNF-α). TNF-α was detected within cytoplasmic lipid bodies of several cell types present on colonic Crohn's disease biopsies, including infiltrating eosinophils (Beil et al 1993). Recently, TNF-α was also found within lipid bodies of circulating neutrophils of septic patients and murine infiltrating neutrophils of experimentally induced sepsis (Pacheco et al 2002).…”
Section: Are Pre-formed Cytokines Stored Within Other Eosinophil Intrmentioning
confidence: 99%
“…Cytoplasmic lipid bodies of isolated human lung mast cells contain the basic fibroblast growth factor (bFGF), also found within mast cell secretory granules . Specifically within eosinophils, the presence of TNF-α (Beil et al 1993) and the lymphocyte chemoattractants RANTES and IL-16 has been detected at lipid bodies. It is noteworthy that TNF-α, RANTES and IL-16 are largely stored within eosinophil specific granules.…”
Section: Are Pre-formed Cytokines Stored Within Other Eosinophil Intrmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it may not be trivial whether workers have given drugs, mediators, etc., intravenously or topically, on the airway mucosa. ERJEFÄLT et al [4], thus, found that topical L-NAME produced a potent exudative response that could not be mimicked by intravenous L-NAME. In the work that prompted the editorial by KUBES [2], only intravenous injections were employed [5].…”
Section: Eosinophil Lysis and Plasma Extravasationmentioning
confidence: 99%
“…Most, if not all, of the cytokines found preformed within eosinophils have been localized to specific granules (4)(5)(6)(7)(8)(9). Strong evidence provided mainly through electron microscopic analyses suggests that the mobilization of these factors from granule stores and subsequent extracellular release follows a process termed "piecemeal" degranulation (PMD), where small cytokine-containing vesicles traffic from granules to the plasma membrane.…”
Section: Introductionmentioning
confidence: 99%